A multi-factor model for the valuation and risk management of demand deposits - Hans Dewachter; Marco Lyrio; Konstantijn Maes (National Bank of Belgium, 2006)
How should we value and manage deposit accounts where deposits have a zero contractual maturity, but which, in practice, remain stable through time and are remunerated below market rates? Does the economic value of the deposit account differ from the face value and can we reliably measure it? To what extent is the economic value sensitive to yield curve changes? In this paper, we try to answer the above questions. The valuation is performed on yield curve, deposit rate and deposit balance data between December 1994 and June 2005 for a sample of Belgian bank retail savings deposits accounts. We find that the deposits premium component of Belgian savings deposits is economically and statistically significant, though sensitive to assumptions about servicing costs and outstanding balances average decay rates. We also find that deposit liability values depreciate significantly when market rates increase, thereby offsetting some of the value losses on the asset side. The hedging characteristics of deposit accounts depend primarily on the nature of the underlying interest rate shock (yield curve level versus slope shock) and on the average decay rate. We assess the reliability of the reported point estimates and also report corresponding duration estimates that results from a dynamic replicating portfolio model approach more commonly used by large international banks.
Keywords: G12; G21; 330; Demand deposits; ALM; risk management; arbitrage free pricing; flexible-affine term structure model; interest rate risk; IFRS 39; fair value accounting; Privatkundengeschäft; Einlagengeschäft; Rendite; Zinsrisiko; IFRS; Belgien; Fair-Value-Bilanzierung